2003
DOI: 10.1002/jlcr.709
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4‐[18F]fluoroiodobenzene and its application in sonogashira cross‐coupling reactions

Abstract: The first application of a Sonogashira cross‐coupling reaction in 18F chemistry has been developed. The reaction was exemplified by the cross‐coupling of terminal alkynes (ethynylcyclopentyl carbinol 6, 17α‐ethynyl‐3,17β‐estradiol 7 and 17α‐ethynyl‐3‐methoxy‐3,17β‐estradiol 8) with 4‐[18F]fluoroiodobenzene. 4,4′‐Diiododiaryliodonium salts were used as precursors for the synthesis of 4‐[18F]fluoroiodobenzene, enabling the convenient access to 4‐[18F]fluoroiodobenzene in 13–70% yield using conventional heating o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 21 publications
(16 reference statements)
1
28
0
1
Order By: Relevance
“…These benefits have resulted in much recent interest in diaryliodonium salts as precursors to fluorine-18 arenes [10][11][12][13][14][15][16], however we, and others [12,16], have observed that the fluoridation results can be extremely variable, particularly in the case of electron-rich diaryliodonium salts. Despite the potential benefits the approach has for the introduction of fluorine-18 into aromatic systems the associated lack of reproducibility has severely limited the development and application of this approach to the production of fluorine-18 labelled radiopharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…These benefits have resulted in much recent interest in diaryliodonium salts as precursors to fluorine-18 arenes [10][11][12][13][14][15][16], however we, and others [12,16], have observed that the fluoridation results can be extremely variable, particularly in the case of electron-rich diaryliodonium salts. Despite the potential benefits the approach has for the introduction of fluorine-18 into aromatic systems the associated lack of reproducibility has severely limited the development and application of this approach to the production of fluorine-18 labelled radiopharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]4-Fluoroiodobenzene 33 and [ 18 F]fluorobromobenzene 34 have been prepared from the radiofluorination of diaryliodonium salts without noticeable concomitant halogen displacement. We have also previously observed resistance to aryl halogen displacement by S N Ar when in well-activated positions in (halopyridinyl)aryliodonium salts during their radio-fluorinations to produce [ 18 F]fluorohalopyridines.…”
Section: Resultsmentioning
confidence: 99%
“…Elaboration of EE 2 is readily achieved using palladium catalyzed Sonogashira cross coupling with halide reagents,24 allowing attachment of a benzaldehyde moiety for ACD conjugation. Subsequent reduction of benzaldehyde 4 gave the benzyl alcohol 5 that was used as a control compound.…”
Section: Resultsmentioning
confidence: 99%